Appraisal of Cinnamaldehyde Analogs as Dual-Acting Antibiofilm and Anthelmintic Agents - Khadke, Sagar Kiran; Lee, Jin-Hyung; Kim, Yong-Guy; Raj, Vinit; Lee, Jintae (Frontiers in Microbiology, 2022)
Cinnamaldehyde has a broad range of biological activities, which include antibiofilm and anthelmintic activities. The ever-growing problem of drug resistance and limited treatment options have created an urgent demand for natural molecules with antibiofilm and anthelmintic properties. Hence, we hypothesized that molecules with a scaffold structurally similar to that of cinnamaldehyde might act as dual inhibitors against fungal biofilms and helminths. In this regard, eleven cinnamaldehyde analogues were tested to determine their effects on fungal Candida albicans biofilm and nematode Caenorhabditis elegans. α-Methyl and trans-4-methyl cinnamaldehydes efficiently inhibited C. albicans biofilm formation (> 90% inhibition at 50 µg/mL) with minimum inhibitory concentrations (MICs) of ≥ 200 µg/mL and 4-bromo and 4-chloro cinnamaldehydes exhibited anthelmintic property at 20 µg/mL against C. elegans. α-Methyl and trans-4-methyl cinnamaldehydes at 50 µg/mL inhibited hyphal growth and cell aggregation. Scanning electron microscopy was employed to determine the surface architecture of C. albicans biofilm and cuticle of C. elegans, and confocal laser scanning microscopy was used to determine biofilm thicknesses. The perturbation in gene expression of C. albicans was investigated using qRT-PCR analysis and α-methyl and trans-4-methyl cinnamaldehydes exhibited down-regulation of ECE1, IFD6, RBT5, UCF1, and UME6 and up-regulation of CHT4 and YWP1. Additionally, molecular interaction of these two molecules with UCF1 and YWP1 were revealed by molecular docking simulation. Our observations collectively suggest α-methyl and trans-4-methyl cinnamaldehydes are potent biofilm inhibitors and that 4-bromo and 4-chloro cinnamaldehydes are anthelmintic agents. Efforts are required to determine the range of potential therapeutic applications of cinnamaldehyde analogues.